Future of the patent system - Shimanami, Ryo (ed.) (Cheltenham, 2012)
In a rapidly changing world, the underlying philosophies, the rationale and the appropriateness of patent law have come under question. Scholars and practitioners from Japan, the US, Europe, India, Brazil and China give detailed analyses of current and likely future problems with their respective systems, and outline possible responses to them.
Keywords: Patents